101 30-Day Outcomes of Resolute Onyx Stent for Symptomatic Intracranial Stenosis: A Multicenter Propensity-Score Matched Comparison With SAMMPRIS Trial. (April 2023) - Siddiq, Farhan; Nunna, Ravi Shankar; Khan, Inamullah; Khan, Musharaf; Beall, Jonathan; Tekle, Wondwossen; Ezzeldin, Mohamad; Tanweer, Omar; Burkhardt, Jan-Karl; Jabbour, Pascal; Tjoumakaris, Stavropoula I.; Herial, Nabeel; et al.
Abstract : INTRODUCTION: Symptomatic intracranial atherosclerotic disease (sICAD) is estimated to cause over 10% of strokes annually in the US alone. Previous investigations employing stenting, most notably SAMMPRIS trial, have produced unfavorable results in regards to both periprocedural complications and risk of recurrent stroke. However, newer generation balloon-mounted drug-eluting stents (BM-DES) have been hypothesized to harbor several technical advantages that may confer improvements in these critical metrics. METHODS: Prospectively maintained databases from eight comprehensive stroke centers were reviewed to identify adult patients undergoing RO-ZES for the treatment of sICAD between January, 2019 and December, 2021. Only patients that presented with either recurrent stroke or TIA, intracranial stenosis 70-99%, with at least one stroke on best medical management were included. The primary outcome was 30-days composite of stroke, ICH, and/or mortality. A propensity-score matched analyses was performed comparing the results of RO-ZES to the intervention arm of SAMMPRIS. RESULTS: A total of 132 patients met the inclusion criteria for analysis (mean age:64.2 years). Mean severity of stenosis (±SD) was 81.4% (±11.4%). Four (3.03%) stroke and/or deaths were reported within 30 days in RO-ZES group. A propensity-score matched analysis based on age, HLD, HTN, DMII, and smoking demonstrated a statistically significant decreased risk of 30-day stroke and/or death rate in RO-ZES in comparison to SAMMPRIS (2.6% vs. 15.6%, respectively; OR 6.88, 95% CI 1.92-37.54, p < 0.001). CONCLUSIONS: Patients treated with RO-ZES had a decreased rate of 30-day major complications in comparison to SAMMPRIS. Further large-scale prospective studies are warranted to evaluate the safety and efficacy of RO-ZES for the treatment of sICAD.